The Linear Theory of Economic Development - Loubaki, Diana (IJRDO - Journal of Applied Management Science, 2017)
This article is a theory of economic development which shows that under development and civil wars in Africa comes mostly from ethnic divisions. Therefore, since development economics dynamics is linear, development take-off is reached at the locus on the space-time where all the ethnics take place inside the production sector without distinction of their origins. Thus, the article promotes incentives to invest in human capital accumulation and labour force participation in the society as a mechanics of economic development since it may fight ethnic division in least advanced economies.